P220 Child sexual exploitation and the association with sexually transmitted infections in under 16 year olds attending genitourinary medicine clinics. (8th June 2017) - Ward, Chris; Hughes, Gwenda; Mitchell, Holly; Rogstad, Karen
Abstract : Introduction: Child sexual exploitation (CSE) can be difficult to identify, with few clinical symptoms or signs. There is limited evidence that markers such as sexually transmitted infections (STIs) are predictors of CSE. We present updated data and analysis from a study investigating the relationship between STI presentation at sexual health clinics (SHCs) and CSE. Methods: SHCs with >18 STI diagnoses in 13–15 year-olds in 2012 were identified using the genitourinary medicine clinic activity dataset (GUMCAD). Cases with confirmed bacterial or protozoal STIs were matched by age, gender and clinic with non-STI controls. Lead clinicians were asked to complete an online questionnaire on CSE-related risk factors irrespective of STI presence. Associations between STI outcome and CSE-related risk factors were analysed using conditional logistic regression. Results: Data was provided on 466 13-15 year-olds; 414 (88.8%) were female. 340 (80.0%) were aged 15, 108 (23.2%) 14 and 18 (3.9%) 13. In matched univariate analysis, an STI diagnosis was significantly associated with 'highly-likely/confirmed' CSE (OR 3.87, p=0.017) and safeguarding concerns (OR 1.94, p=0.022). A weak association between STI diagnosis and 'highly-likely/confirmed' CSE persisted after adjustment for partner numbers and prior clinic attendance (OR 3.85, p=0.053). Discussion: Presentation with bacterial or protozoal STIs by 13–15 year-olds at SHCs may be considered a potential marker for CSE. It would be prudent to consider CSE, in depth assessment and potential referral for any under 16 year-old presenting with an STI.